Analisa Pemasangan Kapasitor Bank Di Gi Pauh Limo Sebagai Akibat Kegagalan Operasi Unit Pembangkit - Lusi Novia Werdian; Edy Ervianto; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Pauh limo substation located in padang west Sumatra has one bank capacitor. This research of evaluate the effect of capacitor installation at the Pauh Limo substation when one of the generating units experiences a trip / disturbance. To find out how much influence the voltage correction due to the installation of capacitors to improve the voltage when the power unit operation fails which results in a voltage drop can be determined by making a simulation using ETAP 12.6.0 software. When a trip occurs in the Ombilin power plant, the voltage at each GI experiences a varying voltage drop. So that the voltage at GI LBALG has the highest voltage, namely 147.5 kV, and GI SHARU has a voltage of 146.5 kV. When the simulation results of the power flow are in normal conditions without the installation of capacitor banks at the PLIMO GI, the GI PIP substation has the highest voltage, namely 145.5 kV, Meanwhile, GI SHARU has a voltage of 144.1 kV which is the lowest voltage. The lowest voltage drop percentage is 4.09% in GI SHARU. Meanwhile, during normal conditions, with the installation of the INDRG GI capacitor, it has the highest voltage, namely 148.4 kV, and GI SHARU has the lowest voltage, namely 147.5 kV. The lowest percentage of voltage drop is 1.69%. Comparison of the GI voltage without capacitor installation under normal conditions and the ombilin trip GI LBALG generator operates in swing mode, so that the voltage at the LBALG GI will remain the same at the 147.5 kV level. Meanwhile, the GI voltage with the installation of the capacitor under normal conditions and the overall ombilin generator trip, the INDRG GI experienced the largest voltage drop, namely 147.3 with a voltage drop of 0.746775%. Keywords: Transmission System, Substation, Capacitor Bank, Voltage Drop,Software ETAP 12.6.0.